Testing and Implementation of Different Wireless Sensor Net-work Algorithms in Agriculture Area - S. Awati, Jayashree; M. R. Patil, Dr.; S.. A. Patil, Dr. (International Journal of Engineering and Technology, 2018)
The paper demonstrates the Testing and Implementation of Different Wireless Sensor Network Algorithms in Agriculture Area. From this algorithm, it will be finalized that which algorithm is more suitable in agriculture area. Agriculture areas are large areas geographically, so to monitor agriculture parameters the wireless sensor networks are more suitable. Graham, Jevis, LPCN l algorithms explained and one personal algorithm implemented. All the results of algorithms are explained in the paper. The results are obtained using wireless network simulator.Â